2019
DOI: 10.2478/johr-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Economic Aspects in the Raspberry Production on the Example of Farms from Poland, Serbia and Ukraine

Abstract: For many years Poland and Serbia have played the dominating roles in European raspberry production. However, the growing production in Ukraine might threaten the relative stability of the raspberry market for both countries. It is projected that in the coming years Ukraine will strengthen its competitive position in relation to the current industrial raspberry production leaders. This justifies the need to conduct comparative analyses of competitive power, and its contributory factors, including production cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Given the commercial production of its fruit, Rubus idaeus has considerable economic importance in Europe and Poland [ 22 , 23 , 24 , 25 , 26 , 27 ]. Raspberry fruit is intended either for direct consumption or for processing in many industries: food [ 20 , 28 , 29 , 30 , 31 ], pharmaceutical [ 20 , 28 , 32 , 33 ], cosmetic [ 28 , 30 , 33 , 34 , 35 , 36 ], and nanotechnological [ 37 , 38 , 39 , 40 ] industries.…”
Section: Introductionmentioning
confidence: 99%
“…Given the commercial production of its fruit, Rubus idaeus has considerable economic importance in Europe and Poland [ 22 , 23 , 24 , 25 , 26 , 27 ]. Raspberry fruit is intended either for direct consumption or for processing in many industries: food [ 20 , 28 , 29 , 30 , 31 ], pharmaceutical [ 20 , 28 , 32 , 33 ], cosmetic [ 28 , 30 , 33 , 34 , 35 , 36 ], and nanotechnological [ 37 , 38 , 39 , 40 ] industries.…”
Section: Introductionmentioning
confidence: 99%
“…2 of 27 berry production's most time-consuming and economically costly processes. It is known that manual harvesting accounts for up to 70% of production costs [11,12,13]. Most cultivars of black and red currants do not meet the modern requirements of industrial cropping because of low adaptability to abiotic and biotic stresses and low suitability for mechanized harvesting [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This is not what any society wants, sending very bad message to the future generations who are full of enthusiasm but also experientially acquired knowledges. Wróblewska et al (2019) dealt with the analysis of raspberry production and comparative analysis on the example of Serbia, Poland and Ukraine. The results showed that Ukraine is a growing power in raspberry production.…”
Section: Introductionmentioning
confidence: 99%